The limits of lead (Pb) phytoextraction and possibilities of phytostabilization in contaminated soil: a critical review. Issue 9 (28th July 2020) - Egendorf, Sara Perl; Groffman, Peter; Moore, Gerry; Cheng, Zhongqi
Abstract: This review article focuses on lead (Pb), one of the most ubiquitous and harmful toxicants found in soil. Our objective is to address misconceptions regarding the ability of plants to uptake Pb through their roots and translocate it to above-ground tissues, and their ability to act as hyperaccumulators and thereby phytoextract Pb. In accordance with a number of cited definitions, we suggest that species capable of Pb phytoextraction can be rated with the following three criteria: (1) root uptake above a nominal threshold of 1, 000 mg Pb/kg, (2) bioconcentration factor (BCF or shoot/soil concentration) >1, and (3) translocation factor (TF or shoot/root concentration) > 1. We review the literature in the updated USDA Phytoremediation Database and conclude that without amendments: no plant has met all three criteria; no plant has been confirmed as a Pb hyperaccumulator. Our analysis suggests that Pb phytoextraction is not a viable remediation option. Pb phytostabilization, however, may be an effective remediation tool in a variety of settings. Planting some of the many species capable of tolerating soil Pb exposure and sequestering it in or around the root zone will limit Pb movement into other ecosystems, prevent resuspended dusts, and mitigate Pb exposure.